An integrated approach using microtremor data for field development and reservoir monitoring: an example from Betung Field, Jambi. Issue 1 (October 2021) - Pascarizativa, R.; Haris, A; Alwi, M S A
Abstract: Reservoir monitoring is one of the most important aspects in oil and gas field management, because it provides industries with the required data in hydrocarbon optimization. This is often carried out in Indonesia by the TAC Pertamina-Pusako Betung Muaro Senami Jambi (PBMSJ), an organization responsible for the management and coordination of oil well activities. In 2012, the organization conducted passive seismic data acquisition and series of drilling campaigns, which successfully increased oil production in Betung Block from 43 to 652 bopd. This campaign was successfully carried out through one and two wells in 2013 and 2014, respectively. Furthermore, the pre-2017 interpretation describes the Betung Anticline as a relatively symmetrical and low angle N-S trending field, which defies the South Sumatra Basin Northwest-Southeast regional trend. This anticline, bound by two high angle normal faults, is unable to define the LKO/OWC position, leading to the consideration of a more integral interpretation approach by the PBMSJ team in early 2017. The procedure was conducted through the use of a 2d seismic line bounded with new wells and SRTM imagery, to combine subsurface structural data with the surface fundamental analogue. In 2017, a passive seismic study was repeatedly conducted in the Betung field, with only 30 measuring points. The urgency in identifying the reservoir is essential within the petroleum industry, in order to produce sufficient hydrocarbons. It is also essential in confirming the potential uses of microseismic data in storage decision-making, through a dataset acquired in Betung, based on reservoir management.